Revision of some types of North American aleocharines (Coleoptera: Staphylinidae: Aleocharinae), with synonymic notes - Gusarov, Vladimir I. (Zootaxa, 2003)
Based on my revision of the types of Nearctic aleocharine staphylinids numerous nomenclatural and taxonomic changes are proposed. The following taxa are transferred: Acrimea acerba Casey, 1911a to Tinotus Sharp, 1883; Moluciba grandipennis Casey, 1911a to Oxypoda Mannerheim, 1830; Paradilacra Bernhauer, 1909 to subtribe Tachyusina Thomson, 1859 of tribe Oxypodini Thomson, 1859; Atheta angusticornis Bernhauer, 1907 to Boreophilia Benick, 1973; At. coriaria (Kraatz, 1856) (originally described in Homalota Mannerheim, 1830) to Dalotia Casey, 1910a; Homalota ambigua Erichson, 1839 to Strigota Casey, 1910a; Pseudousipalia microptera Lohse in Lohse et al., 1990 to Emmelostiba Pace, 1982; and Sableta brittoni Casey, 1911a to Thamiaraea Thomson, 1858. The following new synonymies are established: Acrimea Casey, 1911a with Tinotus Sharp 1883; Acri. fimbriata Casey, 1911a with Ti. trisectus Casey, 1906; Acri. resecta Casey, 1911a with Ti. acerbus (Casey, 1911a); Ancillota Casey, 1910a and Moluciba Casey, 1911a with Oxypoda Mannerheim, 1830; Anc. sollemnis Casey, 1910a, O. vetula Casey, 1911a, O. neptis Casey, 1911a and O. schaefferi Notman, 1920 with O. amica Casey, 1906; Atheta lanei Casey, 1910a and At. nomadica Casey, 1910a with At. graminicola (Gravenhorst, 1806); Homalota polita Melsheimer, 1844, At. disjuncta Casey, 1910a, At. replicans Casey, 1910a, At. spadix Casey, 1910a and At. bucolica Casey, 1910a with At. aemula (Erichson, 1839); At. innocens Casey, 1910a, At. achromata Casey, 1911a and At. profecta Casey, 1911a with At. keeni Casey, 1910a; Dimetrota dempsterensis Lohse in Lohse et al., 1990 with At. prudhoensis (Lohse in Lohse et al., 1990); At. aperta Casey, 1910a, At. wrangelica Casey, 1911a, At. morbosa Casey, 1911a, At. intacta Casey, 1911a and At. alaskana Casey, 1911a with At. picipennis (Mannerheim, 1843); At. leviceps Casey, 1910a, Dimetrota sectator Casey, 1910a, Dim. retrusa Casey, 1910a, Datomicra hebescens Casey, 1910a, Dat. insolida Casey, 1910a, Dat. pellax Casey, 1910a and Pseudota vana Casey, 1911a with At. hampshirensis Bernhauer, 1909; At. repexa Casey, 1911a with At. brumalis Casey, 1910a; At. querula Casey, 1910a, At. socors Casey, 1911a, Dimetrota resima Casey, 1910a, Dim. vigilans Casey, 1910a, Dim. immerita Casey, 1911a, Dim. incredula Casey, 1911a, Dim. opinata Casey, 1911a and Dim. cerebrosa Casey, 1911a with Atheta fenyesi Bernhauer, 1907; At. crassicornis virginica Bernhauer, 1907, At. rhodeana Casey, 1910a, At. capella Casey, 1910a, At. ducens Casey, 1910a, At. temperans Casey, 1910a, At. logica Casey, 1910a, At. tradita Casey, 1911a, At. fenisex Casey, 1911a, At. vierecki Casey, 1911a, At. auguralis Casey, 1911a and At. bifaria Casey, 1911a with At. modesta (Melsheimer, 1844); At. comitata Casey, 1910a, At. gnoma Casey, 1910a, At. elota Casey, 1910a, At. insidiosa Casey, 1910a, Pseudota puricula Casey, 1911a, At. candidula Casey, 1911a, At. diffisa Casey, 1911a, At. nata Casey, 1911a, At. modiella Casey, 1911a and At. vacillans Casey, 1911a with At. frosti Bernhauer, 1909; At. mollicula Casey, 1910a, Sableta phrenetica Casey, 1910a, At. callens Casey, 1911a, At. franklini Casey, 1911a and At. postulans Casey, 1911a with At. ventricosa Bernhauer, 1907; At. cephalina Casey, 1910a, At. nympha Casey, 1910a, At. discreta Casey, 1910a: 42 (nec Casey, 1893, nec Casey, 1910a: 79), Pseudota dissensa Casey, 1910a, At. villica Casey, 1911a and At. disca Moore & Legner, 1975 with At. klagesi Bernhauer,1909; At. citata Casey, 1910a, At. evecta Casey, 1910a, At. propitia Casey, 1911a, At. palpator Casey, 1911a, At. burra Casey, 1911a and At. nacta Casey, 1911a with At. annexa Casey, 1910a; At. sumpta Casey, 1911a with At. concessa Casey, 1911a; At. punctata Blatchley, 1910, Synaptina merica Casey, 1910a and Sy. consonens Casey, 1910a with At. festinans (Erichson, 1839); Boreostiba hudsonica Lohse in Lohse et al., 1990 with At. parvipennis Bernhauer, 1907; Boreophilia chillcotti Lohse in Lohse et al., 1990 with At. blatchleyi Bernhauer & Scheerpeltz, 1926; Datomicra decolorata Casey, 1910a, Dat. inopia Casey, 1910a, Dat. schematica Casey, 1910a and Dat. stilla Casey, 1910a with At. dadopora Thomson, 1867; Boreophilia caseyiana Lohse in Lohse et al., 1990 with Boreophilia nomensis (Casey, 1910a); Metaxya plutonica Casey, 1910a with Boreophilia angusticornis (Bernhauer, 1907); Boreostiba lamellifera Lohse in Lohse et al., 1990 with Boreostiba frigida (J. Sahlberg, 1880); At. laurentiana Blatchley, 1910 with Aloconota sulcifrons (Stephens, 1832); At. immigrans Easton, 1971 with Adota maritima (Mannerheim, 1843); Pseudota miscella Casey, 1910a, Dimetrota pectorina Casey, 1910a and Dim. crucialis Casey, 1910a with Dalotia coriaria (Kraatz, 1856); Dimetrota revoluta Casey, 1910a and Datomicra vaciva Casey, 1910a with Dochmonota rudiventris (Eppelsheim, 1886); At. insolens Casey, 1910a, Dimetrota resplendens Casey, 1910a and At. apposita Casey, 1911a with Liogluta nitens (Mäklin in Mannerheim, 1852); Achromata Casey, 1893 with Mocyta Mulsant & Rey, 1874a; Achromata fusiformis Casey, 1893, Dimetrota nuptalis Casey, 1910a, Acrotona lividula Casey, 1910a and Acro. adjuvans Casey, 1910a with Mocyta fungi (Gravenhorst, 1806); Acrotona digesta Casey, 1910a, Acro. severa Casey, 1910a, Acro. shastanica Casey, 1910a, Acro. prudens Casey, 1910a, Acro. ardelio Casey, 1910a, Acro. renoica Casey, 1910a and Acro. malaca Casey, 1910a with Mocyta breviuscula (Mäklin in Mannerheim, 1852); Eustrigota Casey, 1911a with Acrotona Thomson, 1859; Colpodota inceptor Casey, 1910a, C. abdicans Casey, 1910a, C. repentina Casey, 1910a, C. laxella Casey, 1910a, C. pupilla Casey, 1910a and Strigota seclusa Casey, 1911a with Acrotona sonomana (Casey, 1910a); Anaduosternum Notman, 1922 with Strigota Casey, 1910a; Strigota oppidana Casey, 1910a, St. gnava Casey, 1910a, St. verecunda Casey, 1910a, St. assueta Casey, 1910a, St. mediocris Casey, 1910a, St. vapida Casey, 1910a, St. inculta Casey, 1910a, St. placata Casey, 1910a, St. recta Casey, 1911a, Anaduosternum brevipennis Notman, 1922 and Atheta notmani Moore & Legner, 1975 with St. ambigua (Erichson, 1839); Pseudousipalia Lohse in Lohse et al., 1990 with Emmelostiba Pace, 1982; Fusalia Casey, 1911a with Thamiaraea Thomson, 1858; Th. lira Hoebeke, 1988 and Th. paralira Hoebeke, 1994 with Th. brittoni (Casey, 1911a); Drusilla cavicollis Casey, 1906 with Dr. canaliculata (Fabricius, 1787); Leptusa laticollis Notman, 1921 with Le. brevicollis Casey, 1893; Sipalia fontana Casey, 1911a and Pasilia virginica Casey, 1911a with Leptusa elegans Blatchley, 1910; and Pseudota cornicula Casey, 1911a with Placusa vaga Casey, 1911a. Tinotus pallidus Casey, 1911a is removed from synonymy with Ti. caviceps Casey, 1893 and is placed in synonymy with Ti. trisectus Casey, 1906. Atheta granulata (Mannerheim, 1846) (originally described in Homalota) is considered to be a synonym of At. graminicola (Gravenhorst, 1806), which has Holarctic (circumboreal) distribution. Atheta keeni Casey, 1910a is the valid name for At. vasta sensu Klimaszewski & Winchester, 2002. Boreostiba frigida (J. Sahlberg, 1880) is removed from synonymy with Boreostiba sibirica (Mäklin, 1880) and is considered to be a valid species. Leptusa obscura Blatchley, 1910 is removed from synonymy with Le. canonica Casey, 1906 and is considered to be a valid species. The following synonymies are confirmed: Devia congruens (Casey, 1893) with De. prospera (Erichson, 1839); Paradilacra persola Casey, 1910a, Pa. willametta Casey, 1910a, Pa. uintana Casey, 1910a, Pa. glenorica Casey, 1910a, Pa. symbolica Casey, 1911a, Pa. erebea Casey, 1911a, Pa. subaequa Casey, 1911a, Pa. sinistra Casey, 1911a, Pa. memnonia Casey, 1911a, Pa. vulgatulaCasey, 1911a and Pa. deserticola Casey, 1911a with Pa. densissima (Bernhauer, 1909); Atheta carlottae Casey, 1910a with At. picipennis (Mannerheim, 1843); At. maeklini Fenyes, 1820 (replacement name for Homalota moesta Mäklin in Mannerheim, 1852) with At. hampshirensis Bernhauer, 1909; At. fontis Casey, 1911a with At. pennsylvanica Bernhauer, 1907, Leptusa tricolor Casey, 1906, Le. nebulosa Casey, 1911a and Le. iowensis Casey, 1911a with Le. canonica Casey, 1906; Le. seminitens Casey, 1893 with Le. opaca Casey, 1893. Atheta picipennis (Mannerheim, 1843) (ex Homalota) is a nomen protectum and At. picipennis (Stephens, 1832) (ex Aleochara; a junior synonym of At. amicula (Stephens, 1832)) is a nomen oblitum. Lectotypes are designated for Acrimea fimbriata Casey, 1911a, Acri. acerba Casey, 1911a, Acri. resecta Casey, 1911a, Ancillota sollemnis Casey, 1910a, Oxypoda amica Casey, 1906, O. vetula Casey, 1911a, O. neptis Casey, 1911a, O. schaefferi Notman, 1920, O. prospera Erichson, 1839, O. congruens Casey, 1893, Atheta densissima Bernhauer, 1909, At. lanei Casey, 1910a, At. nomadica Casey, 1910a, At. disjuncta Casey, 1910a, At. replicans Casey, 1910a, At. spadix Casey, 1910a, At. keeni Casey, 1910a, At. innocens Casey, 1910a, At. achromata Casey, 1911a, At. profecta Casey, 1911a, At. carlottae Casey, 1910a, At. aperta Casey, 1910a, At. morbosa Casey, 1911a, At. alaskana Casey, 1911a, At. altaica Bernhauer, 1901, At. leviceps Casey, 1910a, At. hampshirensis Bernhauer, 1909, At. brumalis Casey, 1910a, At. repexa Casey, 1911a, At. fenyesi Bernhauer, 1907, At. querula Casey, 1910a, At. socors Casey, 1911a, At. crassicornis var. virginica Bernhauer, 1907, At. rhodeana Casey, 1910a, At. capella Casey, 1910a, At. ducens Casey, 1910a, At. temperans Casey, 1910a, At. logica Casey, 1911a, At. tradita Casey, 1911a, At. fenisex Casey, 1911a, At. vierecki Casey, 1911a, At. auguralis Casey, 1911a, At. bifaria Casey, 1911a, At. frosti Bernhauer, 1907, At. comitata Casey, 1910a, At. gnoma Casey, 1910a, At. elota Casey, 1910a, At. insidiosa Casey, 1910a, At. candidula Casey, 1911a, At. diffisa Casey, 1911a, At. nata Casey, 1911a, At. modiella Casey, 1911a, At. vacillans Casey, 1911a, At. ventricosa Bernhauer, 1907, At. mollicula Casey, 1910a, At. callens Casey, 1911a, At. franklini Casey, 1911a, At. postulans Casey, 1911a, At. klagesi Bernhauer, 1909, Atheta cephalina Casey, 1910a, At. nympha Casey, 1910a, At. discreta Casey, 1910a: 42 (nec Casey, 1893, nec Casey, 1910a: 79), At. citata Casey, 1910a, At. evecta Casey, 1910a, At. propitia Casey, 1911a, At. palpator Casey, 1911a, At. burra Casey, 1911a, At. nacta Casey, 1911a, At. concessa Casey, 1911a, At. punctata Blatchley, 1910, At. parvipennis Bernhauer, 1907, At. caviceps Blatchley, 1910, At. pennsylvanica Bernhauer, 1907, At. angusticornis Bernhauer, 1907, Atheta laurentiana Blatchley, 1910, At. insolens Casey, 1910a, At. apposita Casey, 1911a, Paradilacra persola Casey, 1910a, Pa. willametta Casey, 1910a, Pa. uintana Casey, 1910a, Pa. glenorica Casey, 1910a, Pa. symbolica Casey, 1911a, Pa. erebea Casey, 1911a, Pa. subaequa Casey, 1911a, Pa. sinistra Casey, 1911a, Pa. memnonia Casey, 1911a, Pa. deserticola Casey, 1911a, Aleochara graminicola Gravenhorst, 1806, Ale. nigritula Gravenhorst, 1802, Homalota aemula Erichson, 1839, H. polita Melsheimer, 1844, H. modesta Melsheimer, 1844, H. sodalis Erichson, 1837, H. festinans Erichson, 1839, H. ambigua Erichson, 1839, Dimetrota sectator Casey, 1910a, Dim. retrusa Casey, 1910a, Dim. resima Casey, 1910a, Dim. vigilans Casey, 1910a, Dim. incredula Casey, 1911a, Dim. opinata Casey, 1911a, Dim. cerebrosa Casey, 1911a, Dim. pectorina Casey, 1910a, Dim. crucialis Casey, 1910a, Datomicra hebescens Casey, 1910a, Dat. insolida Casey, 1910a, Dat. decolorata Casey, 1910a, Dat. inopia Casey, 1910a, Dat. schematica Casey, 1910a, Dat. stilla Casey, 1910a, Dat. vaciva Casey, 1910a, Pseudota vana Casey, 1911a, Ps. puricula Casey, 1911a, Ps. dissensa Casey, 1910a, Ps. miscella Casey, 1910a, Sableta phrenetica Casey, 1910a, Sa. brittoni Casey, 1911a, Synaptina merica Casey, 1910a, Sy. consonens Casey, 1910a, Metaxya plutonica Casey, 1910a, Acrotona lividula Casey, 1910a, Acro. adjuvans Casey, 1910a, Acro. digesta Casey, 1910a, Acro. severa Casey, 1910a, Acro. shastanicaCasey, 1910a, Acro. prudens Casey, 1910a, Acro. ardelio Casey, 1910a, Acro. renoica Casey, 1910a, Acro. malaca Casey, 1910a, Colpodota sonomana Casey, 1910a, C. inceptor Casey, 1910a, C. abdicans Casey, 1910a, C. repentina Casey, 1910a, C. laxella Casey, 1910a, C. pupilla Casey, 1911a, Strigota seclusa Casey, 1911a, St. oppidana Casey, 1910a, St. gnava Casey, 1910a, St. verecunda Casey, 1910a, St. assueta Casey, 1910a, St. mediocris Casey, 1910a, St. vapida Casey, 1910a, St. inculta Casey, 1910a, St. placata Casey, 1910a, St. recta Casey, 1911a, Leptusa seminitens Casey, 1893, Le. tricolor Casey, 1906, Le. nebulosa Casey, 1911a, Le. obscura Blatchley, 1910, Le. elegans Blatchley, 1910, Ulitusa pusio Casey, 1906 and Sipalia fontana Casey, 1911a. Oxypoda acuminata (Stephens, 1832) and Atheta dadopora Thomson, 1867 are reported from North America for the first time. North American records of Atheta altaica Bernhauer, 1901 are confirmed.